Evaluation and treatment of hyperglycemia in critically ill patients. - Balloni, Andrea; Lari, Federico; Giostra, Fabrizio (Acta Biomedica Atenei Parmensis, 2017)
The hyperglycemic reaction to stress is part of adaptive metabolic response to critical illness, especially hypoxia, hemorrhage and sepsis. It involves neuro-endocrine and immune pathways leading to the development of insulin resistance and hepatic glucose production by gluconeogenesis and glycogenolysis. Over the last years the concept of stress related hyperglycemia has been replaced by the concept of dysglycemia and its three domains: hyperglycemia, hypoglycemia and glycemic variability. Each of the three domains is independently associated with increased risk of mortality in patients admitted in intensive care unit and non critically ill patients, both medical and surgical. The strongest association with mortality is demonstrated for hypoglycemia, with additive negative effects for hyperglycemia and glycemic variability. The influence of pre-existing diabetes mellitus on the relation of the three domains of dysglycemia with mortality is not clear, suggesting that patients affected by diabetes mellitus may tolerate a larger glucose variability. Advances in continuous glucose monitoring systems and insulin therapy algorithms may reduce the development of glycemic variability and hypoglycemia, but the benefits in clinical practice have not yet been established in clinical trials.